Kontruksi Identitas Katolik dalam Perspektif Teori Konstruktivisme: Narasi Teologis di Era Digital (International Forum of Researchers and Lecturers, 2026)
This study analyzes the construction of Catholic identity in the digital era from the perspective of social constructivism theory. In contrast to traditional identity formation tied to physical spaces like parishes, the digital age has created a dynamic virtual space where Catholic identity is actively shaped through theological narratives on social media. This qualitative research employs critical discourse analysis (CDA) of digital narratives from various theological sources, including papal posts and content from lay Catholic influencers. The findings indicate that Catholic identity is now constructed through digital interaction and participation, which changes how the faithful perceive church authority, form communities, and express their faith. This process has led to a shift from hierarchical authority to an authority that is also built from the ground up by the participation of the laity. Additionally, Catholic communities are transcending geographical boundaries to become